Modeling Type 1 Diabetes Using Pluripotent Stem Cell Technology - Joshi, Kriti; Cameron, Fergus; Tiwari, Swasti; Mannering, Stuart I.; Elefanty, Andrew G.; Stanley, Edouard G. (Frontiers in Endocrinology, 2021)
Induced pluripotent stem cell (iPSC) technology is increasingly being used to create in vitro models of monogenic human disorders. This is possible because, by and large, the phenotypic consequences of such genetic variants are often confined to a specific and known cell type, and the genetic variants themselves can be clearly identified and controlled for using a standardised genetic background. In contrast, complex conditions such as autoimmune Type 1 diabetes (T1D) have a polygenic inheritance and are subject to diverse environmental influences. Moreover, the potential cell types thought to contribute to disease progression are many and varied. Furthermore, as HLA matching is critical for cell-cell interactions in disease pathogenesis, any model that seeks to test the involvement of particular cell types must take this restriction into account. As such, creation of an in vitro model of T1D will require a system that is cognisant of genetic background and enables the interaction of cells representing multiple lineages to be examined in the context of the relevant environmental disease triggers. In addition, as many of the lineages critical to the development of T1D cannot be easily generated from iPSCs, such models will likely require combinations of cell types derived from in vitro and in vivo sources. In this review we imagine what an ideal in vitro model of T1D might look like and discuss how the required elements could be feasibly assembled using existing technologies. We also examine recent advances towards this goal and discuss potential uses of this technology in contributing to our understanding of the mechanisms underlying this autoimmune condition.